Inclusion of students with disabilities in the European Higher Education Area (EHEA): a systematic review - P. Solís-García; A. Barreiro-Collazo; M. Rodríguez-Correa; E. Delgado-Rico; S. Real-Castelao (Cogent Education)
The European Higher Education Area (EHEA), established after the Bologna Declaration with the goal of its implementation by 2010, presents areas for improvement in fulfilling its principle of inclusive and quality education for students. After over a decade of development, a systematic review on the inclusion of students with disabilities was conducted using the Preferred Reporting Items for Systematic review and Meta-Analysis method to understand the interest in this area, measured by the volume of publications, the methodology employed and the themes addressed. The results indicate a high level of research interest, with a tendency towards quantitative investigations and six areas of focus: perceptions and opinions of students with disabilities, attitudes and perceptions towards disability, professional development and teacher training, accessibility and technology in higher education, policies and programs for students with disabilities and barriers and adjustments in the university environment. A common focus emerges, highlighting the existing challenges in achieving a fundamental right: the right to inclusive and quality education within this space. Future research through more extensive and diverse studies is crucial to substantiate the existing findings and apply the identified measures required for enhancing inclusion.